Country Partnership Framework for the Lebanese Republic for the Period FY17-FY22 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2016)
This Country Partnership Framework (CPF) presents the World Bank Group (WBG) program and the associated results framework for Lebanon for the period FY17-FY22. In a fragile and conflict-prone environment, this CPF aims at mitigating the immediate, and potentially long-lasting impact of the Syria crisis on Lebanon, while strengthening state institutions, addressing existing vulnerabilities, and bolstering efforts on longer term development challenges, all through interventions that foster inclusion and shared prosperity. The CPF will work through two focus areas as a way to renew the social contract between the state and the citizens: (i) expand access to and quality of service delivery; and (ii) expand economic opportunities and increase human capital. Through these two focus areas, the WBG will help Lebanon mitigate the economic and social impact of the Syria crisis, safeguard the country’s development gains, and enhance the prospects for stability and development in the coming years. The CPF will contribute to strengthening the relationship between the state and its citizens, a critical ingredient for peace and stability. The CPF will contribute to strengthening the relationship between the state and its citizens, a critical ingredient for peace and stability. The CPF benefited from a series of stakeholder consultations, including those held in connection with the Systematic Country Diagnostic (SCD) and the WBG Gender Strategy.